Descriptions of Two New Species of Simulium (Simulium) (Diptera: Simuliidae) from Tioman Island, Peninsular Malaysia - Takaoka, H.; Sofian-Azirun, Mohd; Belabut, D.M. (National University of Singapore, 2012)
Two new species of black flies, Simulium (Simulium) jasmoni and S. (S.) tiomanense, are described on the basis of adult, pupal and larval specimens collected from Tioman Island, Pahang, Malaysia, and are placed in the tuberosum species-group in the subgenus Simulium (Simulium) Latreille. Simulium (S.) jasmoni, new species, is characterised by the female tarsal claw with a minute subbasal projection, an unusual characteristic within the species-group, and S. (S.) tiomanense, new species, is striking in having a dichoptic male head, a characteristic rarely recorded in the family Simuliidae, as well as the pupal thoracic integument with a pit-like organ near the base of each gill. Taxonomic notes are given to separate these new species from other related species. Â© National University of Singapore.